Compensation and Working Time in relation to Employee Performance - Mulyono, Mulyono; Hendarsyah*, Decky; Bahri, Saiful (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This research aims to analyze empirically and show the influence of compensation and working time on employee performance. This research uses a descriptive quantitative approach with primary and secondary data sources through questionnaires and literature. The research population was all employees at Meskom Agro Sarimas Company Bengkalis totaling 105 people. The sampling technique used simple random sampling while measuring the number of samples used the Isaac and Michael approach size of 79 people. The data analysis technique uses multiple linear regressions with the help of SPSS software. Before the analysis, validity, reliability, classical assumptions, and hypotheses were tested. The research results show that compensation has a positive effect on employee performance. Working time has a positive effect on employee performance. Compensation and working time simultaneously influence employee performance. Theoretically, this research can complement existing theories. Practically, this research can be used as a reference for companies to improve the performance of their employees, especially in terms of compensation and working time. Keyword: Employee Performance; Compensation; Working Time; Management; Company